Seeing Through the Density: A Case of Misleading BMD Results on bone densitometry - Syeda Hadia Najam; Aamna Hassan (Journal of the Pakistan Medical Association, 2025)
Bone mineral densitometry (BMD) using dual-energy X-ray absorptiometry (DXA) is widely recognized as the standard method for evaluating bone density. DXA produces attenuation maps that aid in measuring BMD. Non-relevant findings are commonly observed in DXA images, some of which may influence BMD measurements, while others have limited clinical significance. While opinions vary, the majority of studies suggest that vascular calcifications do not significantly affect BMD. We present a case of an 84-year-old female who presented for BMD evaluation emphasizing the need to consider different confounding factors in results interpretation. Keywords: Bone Mineral Density (BMD) overestimation, Dual-energy X-ray Absorptiometry (DXA), vascular calcifications